Pendekatan Humanistik dalam Internalisasi Nilai-Nilai Keislaman Generasi Milenial melalui Budaya “Ngarung”: Studi Fenomenologi Moderasi Beragama Karang Taruna Kecakot di Kota Kediri - Hanur, Binti Su'aidah; Hubb, Tahta Ahlamil Hubb; Choirina, Eva Ma’rifatul (Proceedings of Annual Conference for Muslim Scholars, 2022)
Youth generation is a potential generation which well known as professional, energic, and inovative generation. They tend to tolerate toward cultural differences and care to their surrounding because they have grown to accept and appreciate what have been existed in their surroundings. There are two youth organisations in Kediri residence which have synergized in developing milenial activities namely “Ngarung or Ngaji Turut Warung”, they are Karang Taruna and Lajnah Matan. Ngarung as an activity to insert islamic knowledge among youth generation is in line with the Indonesia’s Moderate Islam which is one of its indicators is tolerance. This paper tries to investigate how far their successfulness in developing moderate islam in their social life. Fenomenology studies which is developed in this paper would describe how huge the effect resulted from this activity